The basic function of happiness and vivacity from Rumi's point of view - Dalili Saleh, Ali Asghar (2021)
Happiness is one of the effective characteristics in human existence that the human soul and body have received many effects from this emotional aspect of human beings. Although psychologists' definitions of the causes and factors of happiness are different, but everyone agrees on one basis, and that is the essential need of the individual and society to strengthen the dimension of happiness and vitality in human beings, and that this feature can lead to prosperity and growth. Provide progress in the individual and society. This article confirms that the teachings of Jalaluddin Mohammad Rumi seek to provide a bed of happiness, with the difference that happiness is different from the view of Rumi as a religious mystic with the views of other greats. This research intends to study happiness and vitality on the basis of spiritual Masnavi. Access to Rumi's thoughts and ideas is important because his ideas can be considered as a great Muslim poet and mystic and a representative of Islamic mysticism and can be generalized to the thoughts of many of his followers. Our method in this paper is a library based on documentary study and content analysis. According to Rumi, sorrow is one of the means of conduct and the seeker can not be painless and sorrow, and sorrow that is not in the path of growth is unpleasant and sorrow that is in the direction of excellence is valuable and pleasant. Sadness and happiness cause human mental moderation. Wise sorrows should be welcomed and irrational joys should be avoided. Wise sorrows are the path to happiness, and as a result, the dynamism and mobility of the soul destroys many of the sorrows and daily joys and gives true clarity to the human soul.